Polyadenylated RNA and RNA-Binding Proteins Exhibit Unique Response to Hyperosmotic Stress - Zaepfel, Benjamin L.; Rothstein, Jeffrey D. (Frontiers in Cell and Developmental Biology, 2021)
Stress granule formation is a complex and rapidly evolving process that significantly disrupts cellular metabolism in response to a variety of cellular stressors. Recently, it has become evident that different chemical stressors lead to the formation of compositionally distinct stress granules. However, it is unclear which proteins are required for the formation of stress granules under different conditions. In addition, the effect of various stressors on polyadenylated RNA metabolism remains enigmatic. Here, we demonstrate that G3BP1/2, which are common stress granule components, are not required for the formation of stress granules specifically during osmotic stress induced by sorbitol and related polyols. Furthermore, sorbitol-induced osmotic stress leads to significant depletion of nuclear polyadenylated RNA, a process that we demonstrate is dependent on active mRNA export, as well as cytoplasmic and subnuclear shifts in the presence of many nuclear RNA-binding proteins. We assessed the function of multiple shifted RBPs and found that hnRNP U, but not TDP-43 or hnRNP I, exhibit reduced function following this cytoplasmic shift. Finally, we observe that multiple stress pathways lead to a significant reduction in transcription, providing a possible explanation for our inability to observe loss of TDP-43 or hnRNP I function. Overall, we identify unique outcomes following osmotic stress that provide important insight into the regulation of RNA-binding protein localization and function.